Formulasi dan Karakterisasi Tablet Dispersibel Berbasis Nanopartikel untuk Meningkatkan Disolusi dan Stabilitas Formulasi Metformin - Asmal , Adhitama; Nurvianthi , Riska Yuli (Journal of Pharmaceutical and Sciences, 2025)
Metformin therapy for type 2 diabetes mellitus is limited by its very low aqueous solubility and moderate oral bioavailability, factors that may reduce therapeutic effectiveness. Dispersible tablets also offer advantages for geriatric patients with swallowing difficulties. This study aimed to formulate and characterize nanoparticle-based dispersible tablets of metformin to enhance drug dissolution and early physicochemical stability. Metformin nanoparticles were produced via nanoprecipitation and characterized for particle size, polydispersity, zeta potential, and solid-state properties using XRD and DSC, while SEM imaging was used to assess morphology. The nanoparticles were subsequently compressed into dispersible tablets and evaluated according to pharmacopeial standards. The resulting metformin nanoparticles exhibited a mean particle size of 180 ± 20 nm (PDI 0.25, zeta potential −25 mV). XRD and DSC analyses indicated partial amorphization, which was further supported by SEM micrographs showing smooth, spherical particles with uniform distribution. The dispersible tablets complied with compendial specifications and demonstrated markedly improved dissolution compared with the conventional formulation, achieving 88% release at 30 minutes. Following accelerated stability testing at 40 °C/75% RH, assay values remained ≥95%, with no significant changes in dissolution performance (p > 0.05). In conclusion, the nanoparticle-based dispersible tablets successfully enhanced the in vitro dissolution of metformin while maintaining early physicochemical formulation stability, supporting further development toward improved patient acceptability and future bioavailability studies.